Aid for Peace: A Guide to Planning and Evaluation for Conflict Zones - Paffenholz, Thania; Reychler, Luc (Nomos Verlagsgesellschaft mbH & Co. KG, 2007)
Armed conflict has become the overarching challenge for foreign policy and puts development and humanitarian assistance at considerable risk. How to deal with this situation? What to do? A milestone in its field, this guidebook provides conceptual thought and practical support. It leads both practitioner and academic reader through a planning and evaluation process that helps the user to better design development, humanitarian and peacebuilding interventions in conflict prone areas of the world.Based on the state of the art in theory and practice of peacebuilding, planning and evaluation, the book introduces the "Aid for Peace" Approach and walks the user through a systematic and comprehensive step-by-step process. The user understands how to •  analyze and anticipate conflict dynamics and peacebuilding needs; •  plan new interventions and evaluate existing ones;•  map her or his own intervention and assess its relevance for peacebuilding;•  assess the effects of interventions on peace and conflict by making hypotheses of change explicit and operational; •  integrate the conflict and peace lens into standard planning and evaluation procedures and criteria as well as organizational structures; •  combine a strategic with a process understanding in building a vision for peacebuilding for better contributing to conflict transformation and social change.Written for a broad readership, Aid for Peace leads to the creation of an appropriate policy, project or program design for working in conflict zones.